THE EFFECT OF TRAINING AND UTILIZATION OF SIPKD ON COMPETENCY AND ITS IMPACT ON THE QUALITY OF FINANCIAL STATEMENTS IN DHARMASRAYA REGENCY SKPD - Sari, Neli; Heryanto, Heryanto (Archives of Business Research, 2019)
This study tries to examine the effect of training and utilization of SIPKD on competency and its impact on the quality of financial statements in the SKPD of the Dharmasraya Regency. This study uses descriptive quantitative methods. The study population consisted of 60 people from employees. To obtain a valid and realistic instrument, the validity and reliability test, normality test, multicollinearity test and heterocedasticity test were tested. The data analysis technique used is path analysis using the SPSS program. The results of the study show that there is a positive influence provided by training and the use of SIPKD on increasing competency. The value of indirect influence is greater than the value of direct influence. These results indicate that indirectly training through competence has a significant influence on the quality of financial statements in the SKPD of the Regency of Dharmasraya. The empirical findings indicate that in order to increase community satisfaction, the SIPKD of Dharmasraya District needs to pay attention and focus more on improving training and the quality of financial reports.